2022
DOI: 10.21833/ijaas.2022.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of health status, leisure life, and social relationship satisfaction on depression of elderly people who live alone

Abstract: The increasing number of elderly people who live alone has raised serious social issues such as isolation, care problems, and lonely death. In particular, since elderly people who live alone have a higher rate of depression than general elderly people due to disconnection from good health and social life, it is necessary to promote health, form a social network, and increase leisure activities to prevent depression. Therefore, this study used data from the Korea Welfare Panel in 2020 and conducted a regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…(9)And numerous empirical studies have shown that living alone is a risk factor for depressive symptoms in older adults. (10,11)Living with family had a signi cant effect on subjective well-being, life satisfaction, depressive symptoms in older adults. (12)(13)(14) Sleep duration(SD) refers to a natural physiological phenomenon of human and biological beings.…”
Section: Introductionmentioning
confidence: 96%
“…(9)And numerous empirical studies have shown that living alone is a risk factor for depressive symptoms in older adults. (10,11)Living with family had a signi cant effect on subjective well-being, life satisfaction, depressive symptoms in older adults. (12)(13)(14) Sleep duration(SD) refers to a natural physiological phenomenon of human and biological beings.…”
Section: Introductionmentioning
confidence: 96%